2009
DOI: 10.1158/1535-7163.mct-09-0415
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor–related apoptosis-inducing ligand (TRAIL) and paclitaxel have cooperative in vivo effects against glioblastoma multiforme cells

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) in conjunction with microtubule-targeting agents may be a promising novel anticancer treatment strategy. In vitro studies have suggested that relatively low concentrations of TRAIL enhance the lethality of paclitaxel (Taxol) against human cancer cells. The increased efficacy may be due to the triggering of caspase activation, resulting in mitotic checkpoint abrogation and catastrophe. We show here that wild-type p53 protects cells from caspase-dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…Very recently, gingerol was also shown to induce TRAIL-associated apoptosis, by up-regulating TRAIL receptors (DR4, DR5) on one hand and down-regulating Bcl-2 and survivin on the other hand [44]. The concept of increasing TRAIL receptors is further enhanced by the synergistic use of TRAIL and the well known drugs salinomycin [45] and paclitaxel [46] which appeared to stimulate DR4, DR5 expression, thus increasing responsiveness of gliomas to TRAIL. In a similar way TIC 10 via FOXO3A also triggers the expression of both TRAIL and its receptor [47].…”
Section: Tumor Necrosis Factor (Tnf)mentioning
confidence: 99%
“…Very recently, gingerol was also shown to induce TRAIL-associated apoptosis, by up-regulating TRAIL receptors (DR4, DR5) on one hand and down-regulating Bcl-2 and survivin on the other hand [44]. The concept of increasing TRAIL receptors is further enhanced by the synergistic use of TRAIL and the well known drugs salinomycin [45] and paclitaxel [46] which appeared to stimulate DR4, DR5 expression, thus increasing responsiveness of gliomas to TRAIL. In a similar way TIC 10 via FOXO3A also triggers the expression of both TRAIL and its receptor [47].…”
Section: Tumor Necrosis Factor (Tnf)mentioning
confidence: 99%
“…1a) showed a significative augment only in CA patients (from 16.47 ± 0.82 lM in controls to 21.21 ± 1.78 lM in CA group, P = 0.0453), without alteration in the other groups (18.30 ± 1.96 lM in DOX (Table 2) showed significative leucopenia in DOX-treated group (7,714 ± 453.5 cells/mm 3 in CA patients to 7,063 ± 485.5 cells/mm 3 in DOX group, P = 0.0328), nevertheless counting was within the interval considered normal to healthy human blood (4,000-10,000 cells/mm 3 Spearman's test did not show any significative correlation between tested parameters (Fig. 2).…”
Section: Resultsmentioning
confidence: 83%
“…Although systemic chemotherapy has been known as immunosuppressive to most of patients, evidences have demonstrated that antineoplastic drugs present an important immunogenic role during their tumoricidal effect [1], as tumor apoptosis enhancement [2], higher expression of signaling molecules [3][4][5][6], as well as increment in effector cells number [7] and killing potential [8]. Further, these immunological interactions have been recently evidenced as critical points for response to chemotherapy and patients' clinical outcome [9].…”
Section: Introductionmentioning
confidence: 99%
“…Basic research has revealed that TRAIL targets five receptors, one of which is the death receptor expressed in tumor cells, and it can induce apoptosis by binding with that receptor. In contrast, when TRIAL binds to the decoy receptor that is mainly expressed in normal cells, apoptosis may not occur (Dorsey et al, 2009;Na et al, 2010;Piras et al, 2011). Because its effect on cells depends on the distribution of the receptors, TRAIL has a unique antitumor function (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%